Specification and verification of object-oriented software components - Roth, Andreas (KIT Scientific Publishing, 2006)
This work presents a flexible methodology for formally specifying and deductively verifying object-oriented components.It is based on a simple notion of program correctness. Correctness can be achieved with a novel system of proof obligations, which serve as input to a suitable theorem prover.